(untitled) (Collection of research papers «ECONOMIC STRATEGY AND PROSPECTS OF TRADE AND SERVICES SECTOR DEVELOPMENT», 2026)
The article considers the issue of spreading fundraising operations by enterprises (institutions) in the context of actualization of social initiatives in society. The essence of the concept of “fundraising” is studied, and the economic category is clarified, which will allow to fundamentally organize this type of activity in the implementation of social programs. The basic components of fundraising activities are defined with a view to forming sufficient information support for making decisions on finding and obtaining external financial resources, as well as controlling the centers of responsibility for social projects and initiatives. It is proved that in today’s conditions, fundraising operations of organizational structures become objects of accounting, information about which should be disclosed in internal organizational regulations, in particular, accounting policies. The author emphasizes the need to formulate an accounting policy in terms of fundraising operations in enterprises that receive targeted non-current assets and current resources. The organizational aspects of accounting for income and expenses of fundraising activities in accordance with international and national accounting standards are considered. Recommendations are made to strengthen the analytical nature of information in terms of the costs of searching for donors to attract external funds and the costs of implementing socially innovative projects to control and make decisions on their optimization based on the experience gained. The list of primary documents related to the receipt of earmarked funds and funds for the implementation of social projects is determined. In order to generate accounting information on the resources received by types of fundraising in the accounting system of organizational structures, it is proposed to use subaccount 484 “Fundraising” in the context of analytical features by type of assistance. The organizational aspects of accounting for the use of funds for the received current assets for the implementation of social projects are determined. Based on the information needs of the management system of organizational structures, it is recommended to use an organizational model for accounting for fundraising operations of enterprises (institutions) with the allocation of organizational, technical and methodological support. The structured nature of this model will allow building a powerful accounting and analytical service to search for new sources of external resources, establish and maintain communication channels between donors and enterprises-recipients of resources